Stereoselective C−C Oxidative Coupling Reactions Photocatalyzed by Zwitterionic Ligand Capped CsPbBr3 Perovskite Quantum Dots. Issue 50 (8th October 2020) - Yuan, Yucheng; Zhu, Hua; Hills‐Kimball, Katie; Cai, Tong; Shi, Wenwu; Wei, Zichao; Yang, Hanjun; Candler, Yolanda; Wang, Ping; He, Jie; Chen, Ou
Abstract: Semiconductor quantum dots (QDs) have attracted tremendous attention in the field of photocatalysis, owing to their superior optoelectronic properties for photocatalytic reactions, including high absorption coefficients and long photogenerated carrier lifetimes. Herein, by choosing 2‐(3, 4‐dimethoxyphenyl)‐3‐oxobutanenitrile as a model substrate, we demonstrate that the stereoselective (>99 %) C−C oxidative coupling reaction can be realized with a high product yield (99 %) using zwitterionic ligand capped CsPbBr3 perovskite QDs under visible light illumination. The reaction can be generalized to different starting materials with various substituents on the phenyl ring and varied functional moieties, producing stereoselective dl ‐isomers. A radical mediated reaction pathway has been proposed. Our study provides a new way of stereoselective C−C oxidative coupling via a photocatalytic means using specially designed perovskite QDs. Abstract : C−C oxidative dimerizations of α‐aryl ketonitriles are realized by using zwitterionic ligand capped CsPbBr3 perovskite QDs as catalysts under visible light illumination, via a radical mediated reaction pathway. High stereoselectivities of dl ‐isomers were obtained owing to less steric hindrance during the bond formation process. Our study sheds new lights on using lead‐halide perovskite QDs as photocatalysts for stereoselective organic synthesis.